Effect of different conditioning regimens on survival and engraftment for children with hemophagocytic lymphohistiocytosis undergoing allogeneic hematopoeitic stem cell transplantation: A single institution experience. Issue 9 (29th July 2020) - Ali, Salah; Wall, Donna A.; Ali, Muhammad; Chiang, Kuang‐Yueh; Naqvi, Ahmed; Weitzman, Sheila; Gassas, Adam; Gibson, Paul; Brager, Rae; Fernandez, Conrad V.; Crooks, Bruce; Schechter, Tal; et al.
Abstract: Background: Hemophagocytic lymphohistiocytosis (HLH), a rare hyperinflammatory immuneregulatory disorder, is a challenge in hematopoietic stem cell transplantation (HSCT) because of the high rate of mixed chimerism, relapse, and graft failure (GF) unless intensive myeloablative regimens are used. However, historically conventional myeloablative regimens (conv MA) are associated with high toxicity and mortality. Procedure: We retrospectively compared transplant outcomes between three preparative regimens of varying intensities: Conv MA (n = 15), reduced‐intensity conditioning (RIC, n = 12), and a treosulfan‐based reduced‐toxicity conditioning (RTC, n = 9). Results: Patients in the RIC cohort had a higher incidence of mixed donor chimerism and five patients (42%) developed secondary GF ( P  = .002) compared to the other two regimens. There was a higher incidence of veno‐occlusive disease and intensive care unit (ICU) admissions in the Conv MA cohort. With the RTC regimen, there was a similar 2‐year overall survival (89, 73, and 83%; P  = .87), but improved compound EFS (lack of relapse, GF, second transplant or additional donor cell infusions, or death; 89, 73, and 42%, P  = .041) in RTC, Conv MA, and RIC regimen, respectively. Conclusions: The intensity of the preparative regimen has a significant impact on outcome of HSCT for HLH. The newly described treosulfan‐based RTC provides for a stable graft with a reasonable toxicity profile.